Enhanced interdisciplinary communication: development of an interactive thyroid nodule/cancer disease map. (7th September 2018) - Moubayed, Sami P.; Machado, Rosalie; Tuttle, R. Michael; Orloff, Lisa A.; Randolph, Gregory; Hernandez‐Prera, Juan C.; Griffin, Martha J.; Urken, Mark L.
Abstract : Objectives: Deficits related to inadequate clinical communication can result in incorrect diagnoses, inappropriate surgery, incorrect disease stratification, pathologic reporting, and/or interpretation. There are currently no validated or defined solutions to disease‐specific communication with regard to thyroid care. Methods: We propose a solution that could ameliorate problems arising from inadequate disease‐specific communications between physicians through the development of a thyroid disease‐specific database, the Thyroid Care Collaborative. Results: To improve the quality of thyroid nodule and cancer care, we have developed an imaging module for enhanced reporting of ultrasound, cytologic, surgical, and pathologic details that are obtained during the workup and treatment of a patient. Conclusion: The main advantages of this disease‐specific, dynamic, three‐dimensional, anatomic disease map are: 1) portability across institutions and disciplines, 2) disease specificity to thyroid nodule and cancer care, and 3) ability to trigger more detailed evaluation or reconciliation of any change in a patient's status regarding the nature or the extent of a patient's disease. The first and second advantages above have been identified as areas representing opportunities for quality improvement in health informatics research. Laryngoscope, 129:269–274, 2019